Repercussions of the COVID-19 pandemic on child and adolescent mental health: A matter of concern—A joint statement from EAP and ECPCP - Reali, L.; Nijman, R. G.; Hadjipanayis, A.; Del Torso, S.; Calamita, P.; Rafele, I.; Katz, M.; Barak, S.; Grossman, Z. (Frontiers in Pediatrics, 2022)
COVID-19 pandemic and the consequent rigid social distancing measures implemented, including school closures, have heavily impacted children's and adolescents’ psychosocial wellbeing, and their mental health problems significantly increased. However, child and adolescent mental health were already a serious problem before the Pandemic all over the world. COVID-19 is not just a pandemic, it is a syndemic and mentally or socially disadvantaged children and adolescents are the most affected. Non-Communicable Diseases (NCDs) and previous mental health issues are an additional worsening condition. Even though many countries have responded with decisive efforts to scale-up mental health services, a more integrated and community-based approach to mental health is required. EAP and ECPCP makes recommendations to all the stakeholders to take action to promote, protect and care for the mental health of a generation.